Jean-Jacques Rousseau's La Nouvelle Héloise: Some Doctrinal Affiliations - Elliott, Brian A. (My University, 1973)
This study is an investigation of parallels and extensions, in Julie ou la Nouvelle Héloise, of Rousseau's social analysis as established primarily in the Discours sur l'origine de l'inégalité parmi les hommes and Du Contrat social.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures